PENGAKUAN DAN HAK ASUH ANAK LUAR KAWIN (Studi Penetapan No. 456/Pdt.P/2020/PN Jkt.Pst) - Hermawan, Rudy; Heriyani, Endang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Children out of wedlock only have a civil relationship with their mother and their mother's family. To create a civil relationship with a child out of wedlock, the biological father must confess. In practice the biological father can admit it by submitting an application to the District Court. This can be seen in the determination of No. 456/Pdt/P/2020/PN Jkt Pst. The  problem posed is  how the judge's considerationin   granting the  application   for  recognition of biological fathers to illegitimate children in the determination of Number 456/Pdt.P/2020/PN.Jkt.Pst and the factors that cause extramarital custody rights are in  the biological father?. This type of research is normative legal research. Analysis of research data was carried out using a qualitative descriptive method. The results of this study indicate that the judge's consideration in granting the application for acknowledgment of children out of wedlock is because biological fathers want to have legal standing as a father in meeting all the needs of children which are then stated in a Statement of Recognition, and the factors that cause custody of children out of  wedlock goes to the biological father, because the biological father has shown his responsibilities as a father, by paying for childbirth when a child is born out of wedlock, and is able to finance an illegitimate child to adulthood, and the mother of an illegitimate child has handed over custody of the child to the biological father as outlined in the Deed of Agreement on Rights. Parenting made in front of a Notary.